Characterisation of the deuterium recycling at the W divertor target plates in JET during steady-state plasma conditions and ELMs. (1st February 2016) - Brezinsek, S; Wiesen, S; Harting, D; Guillemaut, C; Webster, A J; Heinola, K; Meigs, A G; Rack, M; Gao, Y; Sergienko, G; Philipps, V; Stamp, M F; et al.
Abstract: Experiments in the JET tokamak equipped with the ITER-like wall (ILW) revealed that the inner and outer target plate at the location of the strike points represent after one year of operation intact tungsten (W) surfaces without any beryllium (Be) surface coverage. The dynamics of near-surface retention, implantation, desorption and recycling of deuterium (D) in the divertor of plasma discharges are determined by W target plates. As the W plasma-facing components (PFCs) are not actively cooled, the surface temperature ( T surface ) is increasing with plasma exposure, varying the balance between these processes in addition to the impinging deuteron fluxes and energies. The dynamic behaviour on a slow time scale of seconds was quantified in a series of identical L-mode discharges (JET Pulse Number (JPN) ) by intra-shot gas analysis providing the reduction of deuterium retention in W PFCs by 1/3 at a base temperature ( T base ) range at the outer target plate between 65 °C and 150 °C equivalent to a T surface span of 150 °C and 420 °C. The associated recycling and molecular D desorption during the discharge varies only at lowest temperatures moderately, whereas desorption between discharges rises significantly with increasing T base . The retention measurements represent the sum of inner and outer divertor interaction at comparable T surface . The dynamic behaviour on a fast time scale of ms was studied in a series of identical H-mode discharges (JPN ) and coherent edge-localized mode (ELM) averaging. High energetic ELMs of about 3 keV are impacting on the W PFCs with fluxes of which is about four times higher than inter-ELM ion fluxes with an impact energy of about E im = 200 eV. This intra-ELM ion flux is associated with a high heat flux of about 60 MW m −2 to the outer target plate which causes T surface rise by Δ T = 100 K per ELM covering finally the range between 160 °C and 1400 °C during the flat-top phase. ELM-induced desorption from saturated near-surface implantation regions as well as deep ELM-induced deuterium implantation areas under varying baseline temperature takes place. Subsequent refuelling by intra-ELM deuteron fluxes occurs and a complex interplay between deuterium fuelling and desorption can be observed in the temporal ELM footprint of the surface temperature (IR thermography), the impinging deuteron flux (Langmuir probes), and the Balmer radiation (emission spectroscopy) as representative for the deuterium recycling flux. In contrast to JET-C, a pronounced second peak, ≃ 8 ms delayed with respect to the initial ELM crash, in the D α radiation and the ion flux has been observed. The peak can be related to desorption of implanted energetic intra-ELM D + diffusing to the W surface, and performing local recycling.